Evolution of Free Economic Zones: A Functional Taxonomy - Marandu, Edward E.; Mburu, Paul T.; Amanze, Donatus (Archives of Business Research, 2017)
This study investigates the evolution of Free Economic Zones (FEZs) using the functional criteria. The methodology of the study involved analysis of the literature. The study makes five main revelations. First, the evolution of FEZ is in general consistent with theory of city life-cycle that states that a city will undergo different stages such as birth, growth, flourishing and decline. And at each stage there are several specific challenges concerning its industrial structure, enterprise structure, spatial structure and so on. Second, the study identifies five evolutionary phases of FEZs which are: Free Trade Zones, Export Processing Zones, Science Industrial Parks, Service Economic Zones and Special Economic Zones; each of these basic zones contain several variants. Third, as the typical FEZs evolve they change the focus of their functions both vertically and horizontally. In vertical terms the zones change the focus of their activities from trade related to manufacturing of the traded goods. In horizontal terms the zones expand their scope by embracing more sectors such as services, science and residential issues. Fourth, there is a progressively stronger orientation toward technology and skill intensive manufacturing and services. Fifth, FEZs are attractive to investors because of the existence of policy failures in the greater host economy: as policy reforms happen investors will see no need for staying in the FEZs and the relative significance of FEZs in economic terms can be expected to decline; at this point FEZ and non-FEZ firms would be treated equally. These findings lead to two general guidelines for sustainable zone development in a developing country context. First, policy makers should start by encouraging trade-intensive FEZ activities in the zones, followed by labor-intensive manufacturing; later on upgrade to technology- and skill-intensive manufacturing and services. Second, policy makers should encourage FDI in industries in which the country has comparative advantage; this increases the likelihood that development will be sustained long after FEZ incentives are removed and all firms are being treated equally in an economy.